The Effect of Physical Activity agains the Telomere Length in the Leukocytes Cells of KONI Athletes - Endang Purwaningsih; Titiek Djannatun; Etty Widayanti; Yulia Suciati; Yenni Zulhamidah (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
Telomeres are strands of non coding DNA at the ends of chromosomes that have the primary function to protect DNA from damage and maintain chromosomal stability. Physical exercise will increase the antioxidant activity can increase telomere proteins, lengthen telomeres and or protein networks associated with telomere so that the telomere remains long, or stopping telomere shortening. Telomere length was also associated with age. The purpose of the research was to determine telomere length of leukocyte cells in the KONI (Indonesian National Sports Committee) athletes in Jakarta. The research method is descriptive, by measuring telomere length using quantitative PCR on leukocyte cells. Samples are KONI athletes from several sports, including men and women athletes, with ages between 15-20 years. Used a control group (not athletes) is students of the Faculty of Medicine, University of YARSI. The results showed that there was no significant difference (p 0.05) between telomere length group of athletes with the control group in both sexes. Similarly, telomere length between athlete male with female athletes also showed no significant difference (p 0.05). It was concluded that physical exercise in athletes KONI at the age of 15- 20 years had no effect on telomere length in leukocytes. The results of this study provide information about the telomere length in Indonesian athletes at an early age.